Analisa SWOT Entrepreneur Woman dalam Pengembangan Tadika Alfikh Orchard - Ardila Putri; Rahmayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the development of TADIKA Alfikh Orchard through a comprehensive SWOT analysis, focusing on women's entrepreneurship in early childhood education management in Malaysia. Employing a qualitative descriptive methodology, the research utilized participatory observation and in-depth interviews during an International Community Service Program. The study reveals that women entrepreneurs demonstrate distinctive capabilities in integrating Islamic values with contemporary educational approaches. Key findings highlight the institution's strengths in financial literacy implementation and innovative learning programs, while identifying external opportunities in the growing demand for Islamic-based early childhood education. The research concludes that strategic networking, robust financial management, and continuous professional development are critical for sustainable growth in early childhood educational institutions. The study contributes to the understanding of women's entrepreneurship in educational contexts and provides strategic insights for institutional development in the Southeast Asian educational landscape.